Legality of implementing Kurdistan Region Referendum - Nyan Abdullah Muhammad; Shari Khalid Marouf (QALAAI ZANIST JOURNAL, 2022)
Referendum is one of the strong tools of state-building process and self-determination of nations. Nations express themselves through a peaceful referendum in which they vote on their own desired framework of the wider state and to establish their own way of life. Referendum is an ancient practice and has been implemented in the United State Confederate and France after the French revolution. Recently, it has been implemented in the Kurdistan Region of Iraq in September, 2017. As such, it cannot be overemphasized the critical importance of the need for a referendum, which is an essential tool to safeguard the self-determination of nations all over the world. The process of referendum can be implemented via bilateral agreements between the central and regional governments under the constitution and monitored by relevant international monitoring bodies. Nevertheless, the process can also be conducted unilaterally by regions, federal states and regional governments, in case the central governments are not willing to collaborate. The Kurdish and Catalan Independence Referendums represent the will of the Kurds and Catalans for independence from their respective central governments. These two central governments were annexing Catalonia and the Kurdistan Region of Iraq by force. In the past, the people Catalonia and the Kurdistan Region of Iraq have been trying with various forms of struggle and eandouvers in order to achieve the goal of independence. Owing to a strong legal basis of the referendum, the authorities in the Kurdistan Region and Catalonia have realized that holding a peaceful referendum could be the most effective way of securing independence from their respective occupiers. Despite of the solid legal grounds of referendum, which was held in the Kurdistan Region of Iraq, and the overwhelming majority which voted in the favor of the independence, the results were later suspended by the Kurdistan Regional Government mainly because of the lack of regional and international support it needed.